Comparative transcriptome analysis reveals potentially novel roles of Homeobox genes in adipose deposition in fat-tailed sheep. Issue 1 (December 2017) - Kang, Danju; Zhou, Guangxian; Zhou, Shiwei; Zeng, Jie; Wang, Xiaolong; Jiang, Yu; Yang, Yuxin; Chen, Yulin
Abstract Adipose tissues are phenotypically, metabolically and functionally heterogeneous based on the sites of their deposition. Undesirable fat deposits in the body are often detrimental to animal and human health. To unravel the potential underlying mechanisms governing accumulation of adipose tissues in various regions of the body, i.e., subcutaneous (SAT), visceral (VAT) and tail (TAT), we profiled transcriptomes from Tan sheep, a Chinese indigenous breed with notable fat tail using RNA-seq. Upon comparison, we identified a total of 1, 058 differentially expressed genes (DEGs) between the three adipose types (218, 324, and 795 in SAT/VAT, SAT/TAT, and VAT/TAT, respectively), from which several known key players were identified that are involved in lipid metabolic process, Wnt signals, Vitamin A metabolism, and transcriptional regulation of adipocyte differentiation. We also found that many elevated genes in VAT were notably enriched for key biological processes such as cytokine secretion, signaling molecule interaction and immune systems. Several developmental genes including HOXC11, HOXC12 and HOXC13, and adipose-expressed genes in the tail region, such as HOTAIR_2, HOTAIR_3 and SP9 were specially highlighted, indicating their strong associations with tail fat development in fat-tailed sheep. Our results provide new insight into exploring the specific fat deposition in tail, also contribute to the understanding of differences between adipose depots.